Multidrug-Resistant Strains of Neisseria gonorrhoeae in Greece - Mavroidi, Angeliki (American Society for Microbiology, 2001)
Eighty-seven out of 575 gonococci isolated in Greece from 1991 to 1998 belonged to serovar Bropyst and exhibited resistance to penicillin, tetracycline, erythromycin, and chloramphenicol. Conventional and molecular typing showed three clusters, A, B, and C, that were associated with networks of high- frequency transmitters (cluster A with homosexuals and clusters B and C with refugees from Eastern Europe). Study of one isolate revealed mutations in the penA, mtrR, and porB genes that may explain the multidrug-resistant phenotype.